The Influence of Social Media Marketing and Personal Selling on Consumer Purchase Decisions Through Purchase Interest as a Mediating Variable - Hakim, Mesra Berlyn; Putri, Yushinta Alya; Ariefien, Mesra Surya (Bulletin of Management and Business, 2023)
The research aims to examine the Influence of Social Media Marketing and Personal Selling on Consumer Purchase Decisions Through Purchase Interest as a Mediating Variable. This study is categorized as a survey research, where the research instrument is in the form of a questionnaire. The population in this study consists of all House Of Yush customers who have made purchases throughout Indonesia. The sample includes 100 respondents determined by non-probability sampling using purposive sampling techniques. Data were analyzed using the SPSS for Windows version 26.0 software. The results indicate that the direct influence of social media marketing and personal selling is greater than the indirect influence on purchase decisions through purchase interest. The overall findings imply that social media marketing and personal selling are factors in increasing purchase interest to achieve improved purchase decisions at House Of Yush production house.